Effect of α-Tocopherol in Tris-Aminomethane – Egg Yolk on the Semen Quality during Cold Storage in Boer goats (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2012)
The study was conducted to evaluate the effect of α-tocopherol in  Tris Aminomethane – egg yolk diluent at cold storage in Boer goats. The semen was collected from  Boer goats buck aged 1.5-2 years old,  with a body weight of 80-90 kg.  After evaluation of fresh semen, the semen was diluted with tris-aminomethane-egg yolk with a ratio of 1 : 10. The diluted semen then was divided into four groups containing 0.0 g; 0.2 g; 0.4 and 0.6 g α-tocopherol / 100 ml diluent, and stored at 5oC for one hour before evaluation. The results showed that there was no significant difference in sperm motility, however the sperm viability and abnormality were significantly differences (P<0.01) between groups both before and 1-hour after storage at cold temperature.